Evolutionary process change factor on internal customer satisfaction in telecommunication companies Jordan - Al-Sardia, Sattam Jumah; Ahmad, Hartini (Centre for Promoting Ideas, 2013)
This study investigates the influence of leadership change, behavioural change, structural change, technological change and cultural change on internal customer satisfaction.Due to this, a cross-sectional study design with a quantitative study approach was conducted, and data was generated through self-administered procedure from 354 respondents who are employees of Orange, Zain and Umniah telecommunication companies in Jordan. A regression analysis technique was used to analysis the data.Overall, the findings show that leadership change, behavioural change, structural change, technological change and cultural change are significant predictors of internal customer’s satisfaction in the three major telecommunication companies in Jordan. Based on this, the study concludes that an effective internal customer satisfaction depends on leadership change, behavioural change, structural change, technological change and cultural change.The study contributes to the body of knowledge by providing additional insight into the key factors that affect the internal customer satisfaction.The study also highlights some of its limitations and makes suggestions for future study in this domain.